PENGARUH STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Renalya Renalya; Desy Purwasih (LPPM Universitas Bina Bangsa, 2022)
This study aims to examine the effect of asset structure and sales growth on capital structure with firm size as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The type of research conducted is quantitative research using associative methods. The research sample was determined using a purposive sampling technique, so that a sample of 16 companies could be produced with a total of 80 observation data. The analysis used is panel data regression analysis and moderating regression analysis. The results showed that the variable structure of assets and sales growth simultaneously affect the capital structure. The results of the study partially show that the asset structure variable has a significant effect on capital structure, while the sales growth variable does not have a significant effect on capital structure, the firm size variable cannot moderate the relationship between asset structure and capital structure, and the firm size variable cannot moderate the relationship between sales growth and sales growth. capital structure